Lithium ion battery
By using additives A and B of specific structures in the lithium-ion battery electrolyte and designing channels on the electrodes, the problems of poor low-temperature performance and high-temperature safety hazards of lithium-ion batteries are solved, and the improvement of high-temperature circulation and storage performance is achieved. Improved kinetic performance.
Patent Information
- Application Number
- CN202411562198.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-31
AI Technical Summary
Lithium-ion batteries have poor performance under low temperature conditions, especially the low dielectric constant of linear carbonate and carboxylic acid esters and the low solubility of lithium salts, resulting in a decrease in the migration rate of lithium ions, and the intensification of chemical reactions at high temperatures, leading to safety hazards. The existing measures affect Kinetics performance.
Additives A and B with specific structures are used in the electrolyte solution, combined with the channel design on the positive electrode sheet and the negative electrode sheet to meet a specific proportional relationship to improve the high and low temperature performance and electrochemical performance of lithium-ion batteries.
By improving the electrolyte structure and pole channel design of lithium-ion batteries, the high-temperature cycling, storage performance and kinetic performance of lithium-ion batteries are improved, polarization and impedance are reduced, and electrochemical performance is improved.
Smart Images

Figure BDA0005118183690000021 
Figure BDA0005118183690000031 
Figure BDA0005118183690000041
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in digital electronics, electric vehicles, energy storage applications, and aerospace due to their high operating voltage, long cycle life, high energy density, and environmental friendliness. Electrolyte, as the "blood" of lithium-ion batteries, is one of the important raw materials of lithium-ion batteries. It is responsible for the transmission capacity between the positive and negative electrodes and plays a vital role in the performance of lithium batteries. Solvents, lithium salts, and additives all play an important role in the low temperature, cycle, storage, and safety performance of lithium-ion batteries.
[0003] However, under low temperature conditions, linear carbonates and carboxylates often have low dielectric constants due to their own structural characteristics, and the solubility of lithium salts is low at low temperatures, which leads to a decrease in the migration rate of lithium ions and poor low-temperature performance. The hot box test is one of the important tests for lithium-ion batteries. At extreme temperatures (≥130°C), the internal chemical reaction of the battery continues to intensify and heat cannot be released, causing lithium batteries to catch fire or even explode, posing serious safety hazards. The current solution is mainly to add stable film-forming additives to improve the stability of the positive electrode material and reduce side reactions. However, stable film-forming additives will increase the impedance of the battery system and affect the kinetic performance.
[0004] Therefore, there is an urgent need to develop a lithium-ion battery that can improve high and low temperature performance, cycle performance and hot box performance and has good electrochemical performance. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium ion battery that can improve high and low temperature performance, cycle performance and hot box performance while taking into account good electrochemical performance in view of the deficiencies of the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the electrolyte comprises an additive, wherein the additive comprises an additive A having a structure of the following formula I and an additive B having a structure of the following formula II;
[0008]
[0009] Wherein, R1 is independently selected from any one of alkyl, halogenated alkyl, alkyl substituted by heteroatom group or halogenated heteroatom group, alkenyl, halogenated alkenyl, alkenyl substituted by heteroatom group or halogenated heteroatom group, alkynyl, halogenated alkynyl, alkynyl substituted by heteroatom group or halogenated heteroatom group; the heteroatom includes at least one of O, S, P, N, Si and B; the positive electrode sheet and / or the negative electrode sheet are provided with channels along the thickness direction.
[0010] Preferably, the mass percentage (wt%) of additive A in the electrolyte is A, and the mass percentage (wt%) of additive B in the electrolyte is B.
[0011] Preferably, the width C of the channel is 10-300 μm.
[0012] Preferably, the spacing D between the channels is 0.1-3 mm.
[0013] Preferably, the depth of the hole accounts for 5%-70% of the thickness of the pole piece.
[0014] When the pore spacing is too large, the width is too small, and the depth is too low, the electrolyte transmission path at the negative end is not shortened, but the negative electrode particles are broken and lost, and the performance is reduced; when the pore spacing is too small, the width is too large, and the depth is too high, the negative electrode is severely damaged and the electrical performance deteriorates seriously.
[0015] Preferably, A, B, C, D and E satisfy the following relationship: 0.003≤(A+B) / C≤0.105, 0.25≤(A+B) / D≤5.5, 1≤(A+B) / E≤55.
[0016] Among them, controlling the value of the relationship within a range can improve the battery's high-temperature cycle, storage and other performance while taking into account the dynamic performance.
[0017] When the value of (A+B) / C is too small, it will lead to serious loss of negative electrode capacity of the battery cell; when the value of (A+B) / C is too large, it will cause the electrolyte viscosity to not match the pores and the battery cell dynamics to be insufficient.
[0018] When the value of (A+B) / D is too small, the electrolyte viscosity will not match the pores and the battery cell dynamics will be insufficient. When the value of (A+B) / D is too large, the negative electrode capacity of the battery cell will be seriously lost.
[0019] When the value of (A+B) / E is too small, it will lead to serious loss of negative electrode capacity of the battery cell; when the value of (A+B) / E is too large, it will cause the electrolyte viscosity to not match the pores and the battery cell dynamics to be insufficient.
[0020] Preferably, the additive B comprises at least one compound selected from the following structural formulas:
[0021]
[0022] Preferably, the content of the additive A accounts for 0.1-10.0 wt % of the total mass of the electrolyte; the content of the additive B accounts for 0.1-10.0 wt % of the total mass of the electrolyte.
[0023] Preferably, the electrolyte further comprises a lithium salt, a non-aqueous organic solvent and a film-forming additive.
[0024] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, bisfluorosulfonyl imide lithium salt and bisfluorosulfonyl imide lithium, and the content of the lithium salt accounts for 0.1-15.0wt% of the total mass of the electrolyte.
[0025] Preferably, the non-aqueous organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate and γ-butyrolactone, and the content of the non-aqueous organic solvent accounts for 20.0-70.0wt% of the total mass of the electrolyte.
[0026] Preferably, the film-forming additive is selected from one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, succinonitrile, adiponitrile, ethylene glycol diether and hexane trinitrile, and the content of the film-forming additive accounts for 0.1-20.0wt% of the total mass of the electrolyte.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention provides a lithium ion electrolyte including additive A and additive B. Additive A changes the lithium ion solvation structure in the electrolyte and reduces the lithium ion desolvation energy. Additive B has more cyano groups than traditional low nitrile and has stronger complexing ability for positive electrode transition metal ions, thus improving the stability of the positive electrode. Additive A has lower desolvation energy and can reduce negative electrode impedance growth and polarization when used in combination with additive B. Additive A can also improve the solubility of additive B.
[0029] (2) Additive A and Additive B have high viscosity and poor wettability. Therefore, they need to be matched with the holes set on the electrode to allow the electrolyte to penetrate deeper, shorten the lithium ion transmission path, and thus improve the electrochemical performance of the battery.
[0030] (3) When the values of A, B, C, D and E satisfy the relationship: 0.003≤(A+B) / C≤0.105, 0.25≤(A+B) / D≤5.5, 1≤(A+B) / E≤55, the battery can improve the high temperature cycle, storage and other performances while taking into account the dynamic performance, thereby ensuring the fast charging performance. DETAILED DESCRIPTION
[0031] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] According to the first aspect of the present application, the present application aims to provide a lithium ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the electrolyte comprises an additive, wherein the additive comprises an additive A having a structure of the following formula I and an additive B having a structure of the following formula II;
[0033]
[0034] Wherein, R1 is independently selected from any one of alkyl, halogenated alkyl, alkyl substituted by heteroatom group or halogenated heteroatom group, alkenyl, halogenated alkenyl, alkenyl substituted by heteroatom group or halogenated heteroatom group, alkynyl, halogenated alkynyl, alkynyl substituted by heteroatom group or halogenated heteroatom group; the heteroatom includes at least one of O, S, P, N, Si and B; the positive electrode sheet and / or the negative electrode sheet are provided with channels along the thickness direction.
[0035] The mass percentage (wt%) of additive A in the electrolyte is A, and the mass percentage (wt%) of additive B in the electrolyte is B.
[0036] In some embodiments, the width C of the channel is 10-300 μm, for example, 10 μm, 30 μm, 50 μm, 70 μm, 100 μm, 130 μm, 160 μm, 190 μm, 210 μm, 240 μm, 270 μm, or 300 μm.
[0037] In some embodiments, the spacing D of the channels is 0.1-3 mm. For example, it can be 0.1 mm, 0.3 mm, 0.6 mm, 0.9 mm, 1.3 mm, 1.6 mm, 1.9 mm, 2.3 mm, 2.6 mm, 2.9 mm, 3.0 mm.
[0038] In some embodiments, the depth of the hole accounts for a percentage E of the thickness of the pole piece of 5%-70%, for example, 5%, 15%, 25%, 35%, 45%, 55%, 65%, 70%.
[0039] In some embodiments, A, B, C, D and E satisfy the following relationships: 0.003≤(A+B) / C≤0.105, 0.25≤(A+B) / D≤5.5, 1≤(A+B) / E≤55.
[0040] In some embodiments, (A+B) / C may be, for example, 0.003, 0.01, 0.05, 0.1, or 0.105.
[0041] In some embodiments, (A+B) / D may be, for example, 0.25, 0.35, 0.55, 0.85, 0.55, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 5.0, 5.5.
[0042] In some embodiments, (A+B) / E can be, for example, 1, 10, 20, 30, 40, 50, 55.
[0043] In some embodiments, the additive B comprises at least one compound selected from the following structural formulas:
[0044]
[0045] In some embodiments, the content of additive A accounts for 0.1-10.0wt% of the total mass of the electrolyte, for example, it can be 0.1%, 0.5%, 1.0%, 1.5%, 2.5%, 3.5%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, or 10.0%.
[0046] In some embodiments, the content of additive B accounts for 0.1-10.0wt% of the total mass of the electrolyte, for example, it can be 0.1%, 0.5%, 1.0%, 1.5%, 2.5%, 3.5%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, or 10.0%.
[0047] In some embodiments, the electrolyte further includes a lithium salt, a non-aqueous organic solvent, and a film-forming additive.
[0048] In some embodiments, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, bisfluorosulfonyl imide lithium salt and bisfluorosulfonyl imide lithium, and the lithium salt content accounts for 0.1-15.0wt% of the total mass of the electrolyte.
[0049] In some embodiments, the non-aqueous organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate and γ-butyrolactone, and the content of the non-aqueous organic solvent accounts for 20.0-70.0wt% of the total mass of the electrolyte.
[0050] In some embodiments, the film-forming additive is selected from one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, succinonitrile, adiponitrile, ethylene glycol diether and hexane trinitrile, and the content of the film-forming additive accounts for 0.1-20.0wt% of the total mass of the electrolyte.
[0051] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, copper foil.
[0052] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (where 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S), the positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.
[0053] The separator can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more materials including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0054] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0055] Example 1
[0056] (1) Preparation of electrolyte
[0057] In a glove box filled with argon, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a mass ratio of 1:1:3, and then 14.5wt% of lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution. Finally, 0.5wt% of additive A, 0.4wt% of additive B1, 6wt% of fluoroethylene carbonate (FEC) and 1wt% of diethylene sulfate (DTD) were added to the total weight of the electrolyte, and the electrolyte was obtained after stirring. (2) Preparation of pole pieces
[0058] After the electrode coating is completed, laser etching is performed horizontally along the electrode to form continuous and spaced channels in the electrode. The channel width C is 100 μm, the spacing D is 2 mm, and the depth accounts for 20% of the electrode thickness E.
[0059] (3) Preparation of batteries
[0060] The prepared positive electrode sheet (active material LiCoO2), separator, and negative electrode sheet (active material graphite) are stacked in order, with the separator placed between the positive and negative electrode sheets, and then wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic film outer package, and the prepared electrolyte is injected into the dried battery, packaged, allowed to stand, formed, shaped, and capacity divided to finally obtain a lithium-ion battery.
[0061] Example 2
[0062] Different from Example 1, the content of additive A in this example is 1.0 wt %.
[0063] The rest is the same as Example 1 and will not be described again here.
[0064] Example 3
[0065] Different from Example 1, the content of the additive B1 in this example is 0.2 wt %.
[0066] The rest is the same as Example 1 and will not be described again here.
[0067] Example 4
[0068] Different from Example 1, the content of the additive B1 in this example is 0.6 wt %.
[0069] The rest is the same as Example 1 and will not be described again here.
[0070] Example 5
[0071] Different from Example 1, in this example, the additive B1 is replaced by the additive B2, and the content of the additive B2 is 0.4 wt %.
[0072] The rest is the same as Example 1 and will not be described again here.
[0073] Example 6
[0074] Different from Example 1, in this example, the additive B1 is replaced by the additive B3, and the content of the additive B3 is 0.4 wt %.
[0075] The rest is the same as Example 1 and will not be described again here.
[0076] Example 7
[0077] The difference from Example 1 is that the content of the additive A in this example is 0.1 wt %. The rest is the same as Example 1 and will not be described again.
[0078] Example 8
[0079] The difference from Example 1 is that the content of the additive A in this example is 10 wt %. The rest is the same as Example 1 and will not be described again.
[0080] Example 9
[0081] The difference from Example 1 is that the content of the additive B1 in this example is 0.1 wt %. The rest is the same as Example 1 and will not be described again.
[0082] Example 10
[0083] The difference from Example 1 is that the content of the additive B1 in this example is 10 wt %. The rest is the same as Example 1 and will not be described again.
[0084] Embodiment 11
[0085] Different from the embodiment 1, the channel depth in this embodiment is 5%.
[0086] The rest is the same as Example 1 and will not be described again here.
[0087] Example 12
[0088] Different from the embodiment 1, the channel depth in this embodiment is 70%.
[0089] The rest is the same as Example 1 and will not be described again here.
[0090] Example 13
[0091] Different from the first embodiment, the hole spacing in this embodiment is 0.1 mm.
[0092] The rest is the same as Example 1 and will not be described again here.
[0093] Embodiment 14
[0094] Different from Example 1, the hole spacing in this embodiment is 3 mm.
[0095] The rest is the same as Example 1 and will not be described again here.
[0096] Embodiment 15
[0097] Different from Example 1, the channel width in this example is 10 μm.
[0098] The rest is the same as Example 1 and will not be described again here.
[0099] Example 16
[0100] Different from Example 1, the channel width in this example is 300 μm.
[0101] The rest is the same as Example 1 and will not be described again here.
[0102] Comparative Example 1
[0103] Different from Example 1, additive A and additive B are not added in this comparative example.
[0104] The rest is the same as Example 1 and will not be described again here.
[0105] Comparative Example 2
[0106] The difference from Example 1 is that the depth of the negative electrode channel in this comparative example accounts for 4% of the thickness of the electrode sheet. The rest is the same as Example 1 and will not be repeated here.
[0107] Comparative Example 3
[0108] Different from Comparative Example 2, the depth of the negative electrode channel in this comparison accounts for 75% of the thickness of the electrode sheet.
[0109] The rest is the same as Example 1 and will not be described again here.
[0110] Comparative Example 4
[0111] Different from Example 1, additive A is not added in this comparative example.
[0112] The rest is the same as Example 1 and will not be described again here.
[0113] Comparative Example 5
[0114] Different from Example 1, the content of additive A in this comparative example is 15 wt %.
[0115] The rest is the same as Example 1 and will not be described again here.
[0116] Comparative Example 6
[0117] Different from Example 1, no additive B is added in this comparative example.
[0118] The rest is the same as Example 1 and will not be described again here.
[0119] Comparative Example 7
[0120] Different from Example 1, the content of additive B1 in this comparative example is 15 wt %.
[0121] The rest is the same as Example 1 and will not be described again here.
[0122] Comparative Example 8
[0123] Different from Example 1, the channel spacing in this comparative example is 5 mm.
[0124] The rest is the same as Example 1 and will not be described again here.
[0125] Comparative Example 9
[0126] The difference from Example 1 is that the channel width in this comparative example is 350 μm. The rest is the same as Example 1 and will not be described again.
[0127] The values of the parameters in Examples 1-16 and Comparative Examples 1-9 are shown in Table 1-2 below.
[0128] Table 1
[0129]
[0130]
[0131] Table 2
[0132]
[0133]
[0134] The following performance tests were performed on the lithium ion batteries prepared in the examples and comparative examples:
[0135] (1) DCR (direct current resistance) test: at room temperature (23℃±3℃), constant current and voltage were set at 0.5C to 4.45V, cut-off current was 0.02C, then discharged at 0.1C for 9h (adjusted to 10% SOC), then discharged at 0.1C for 10s, and the end voltage V1 was recorded. Discharged at 1C for 1s, and the end voltage V2 was recorded. DCR calculation formula: DCR = (V1-V2) / (1C-0.1C).
[0136] (2) Low temperature discharge performance: The battery was charged and discharged once at 0.2C at room temperature (4.45V-3.0V), and the battery discharge capacity C0 was recorded. Then, the battery was fully charged at 0.2C at room temperature, and then transferred to a -10℃ environment and discharged at 0.2C. The discharge capacity C1 was recorded. The capacity retention rate at -10℃ and 3.0V was C1 / C0.
[0137] (3) High temperature cycle performance test: At 45°C, the divided battery was charged to 4.45V at 0.7C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 500 cycles of charge and discharge, the capacity retention rate at the 500th cycle was calculated. The calculation formula is as follows: 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%.
[0138] (4) 60℃ 14d high temperature storage test: The battery was placed at room temperature and charged and discharged once at 0.5C (4.45V-3.0V), and the discharge capacity C0 of the battery before storage was recorded. The battery was then charged to 4.45V at constant current and constant voltage. The thickness d1 of the battery before high temperature storage was measured using a PPG battery thickness gauge (500g). The battery was placed in a 60℃ constant temperature box and stored for 14 days. After the storage was completed, the battery was taken out and the thermal thickness d2 of the battery after storage was measured. The battery thickness expansion rate after storage at 60℃ for 14 days was calculated. The battery was heated to room temperature and then cooled to room temperature. After cooling for 24 hours, the battery was discharged at a constant current of 0.5C to 3.0V again, and then charged to 4.45V at a constant current and constant voltage of 0.5C. The discharge capacity C1 and charging capacity C2 of the battery after storage were recorded. The capacity residual rate and recovery rate of the battery after storage at 60℃ for 14 days were calculated. The calculation formulas are as follows: thickness expansion rate after storage at 60℃ for 14 days = (d2-d1) / d1*100%; capacity residual rate after storage at 60℃ for 14 days = C1 / C0*100%; capacity recovery rate after storage at 60℃ for 14 days = C2 / C0*100%.
[0139] The results of the above performance tests are shown in Table 3 below.
[0140] Table 3
[0141]
[0142]
[0143] By comparing the experimental data of Examples 1-16 and Comparative Examples 1-9 in Table 3, it can be seen that the combination of the compound of Formula I and the compound of Formula II can improve the high-temperature cycle and high-temperature storage performances when they are within the set range. When the hole depth, spacing and holes on the electrode are appropriate, the DCR can be reduced without deteriorating the high-temperature storage and the low-temperature discharge can be improved.
[0144] Among them, according to Example 1, when the content of additive A1 is 0.5wt%, the content of additive B1 is 0.4wt%, and the depth of the negative electrode channel accounts for 20% of the thickness of the electrode sheet, the performance of the lithium ion battery is optimal.
[0145] By comparing the experimental results of comparative examples 2-3, 8-9 with those of embodiments 1, 13-16, it can be seen that when the electrode hole depth is shallower or deeper, the spacing is larger and the hole is larger, the impedance is higher, and there is no obvious improvement in high temperature cycling and high temperature storage performance.
[0146] Therefore, this solution not only exhibits excellent high and low temperature performance and fast charging performance, but also effectively improves the cycle and storage performance.
[0147] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, characterized in that: The electrolyte includes additives, wherein the additives include additive A having a structure of the following formula I and additive B having a structure of the following formula II; wherein R1 is independently selected from any one of alkyl, haloalkyl, alkyl substituted with a heteroatom group or a halogenated heteroatom group, alkenyl, haloalkenyl, alkenyl substituted with a heteroatom group or a halogenated heteroatom group, alkynyl, haloalkynyl, alkynyl substituted with a heteroatom group or a halogenated heteroatom group; the heteroatom comprises at least one of O, S, P, N, Si and B; The positive electrode sheet and / or the negative electrode sheet are provided with channels along the thickness direction.
2. A lithium ion battery according to claim 1, characterized in that: The mass percentage (wt%) of additive A in the electrolyte is A, and the mass percentage (wt%) of additive B in the electrolyte is B.
3. A lithium ion battery according to claim 1, characterized in that: The width C of the pores is 10-300 μm, the spacing D between the pores is 0.1-3 mm, and the depth of the pores accounts for a percentage E of 5%-70% of the thickness of the pole piece.
4. A lithium ion battery according to claim 1, characterized in that: A, B, C, D and E satisfy the following relationship: 0.003≤(A+B) / C≤0.105, 0.25≤(A+B) / D≤5.5, 1≤(A+B) / E≤55.
5. A lithium ion battery according to claim 1, characterized in that: The additive B comprises at least one compound selected from the following structural formulas:
6. A lithium ion battery according to claim 1, characterized in that: The content of the additive A accounts for 0.1-10.0 wt% of the total mass of the electrolyte; the content of the additive B accounts for 0.1-10.0 wt% of the total mass of the electrolyte.
7. A lithium ion battery according to claim 1, characterized in that: The electrolyte also includes a lithium salt, a non-aqueous organic solvent and a film-forming additive.
8. A lithium ion battery according to claim 7, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bisfluorosulfonyl imide salt and lithium bisfluorosulfonyl imide, and the content of the lithium salt accounts for 0.1-15.0wt% of the total mass of the electrolyte.
9. A lithium ion battery according to claim 7, characterized in that: The non-aqueous organic solvent is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate and γ-butyrolactone, and the content of the non-aqueous organic solvent accounts for 20.0-70.0wt% of the total mass of the electrolyte.
10. A lithium ion battery according to claim 7, characterized in that: The film-forming additive is selected from one or more of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, propene sultone, citraconic anhydride, succinonitrile, adiponitrile, ethylene glycol diether and hexane trinitrile, and the content of the film-forming additive accounts for 0.1-20.0wt% of the total mass of the electrolyte.
